2008
DOI: 10.1038/leu.2008.276
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of NIH consensus criteria for chronic graft-versus-host disease

Abstract: To assess the applicability of the National Institutes of Health (NIH) consensus criteria (NCC) for chronic graft-versus-host disease (cGVHD), 211 patients who developed GVHD more than 100 days after allogeneic transplantation were reclassified using NCC. Classifications were: late acute GVHD (44 patients, 21%), overlap syndrome (64 patients, 30%) and classic cGVHD (103 patients, 49%). Classic cGVHD and overlap syndrome patients (n ¼ 167) were graded using both the revised Seattle criteria (RSC) and NIH global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 17 publications
4
106
1
1
Order By: Relevance
“…The presence of some of these criteria (thrombocytopenia, extensive skin involvement, progressive onset, weight loss, diarrhoea, low Karnofsky performance score) in a patient may prompt a physician to treat more aggressively at the diagnosis of chronic GVHD. It is now appreciated that some of these criteria may actually point to persistent manifestations of acute GVHD (late acute, overlap syndrome) rather than pure chronic GVHD (Filipovich et al, 2005;Cho et al, 2009;Jagasia et al, 2009).…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…The presence of some of these criteria (thrombocytopenia, extensive skin involvement, progressive onset, weight loss, diarrhoea, low Karnofsky performance score) in a patient may prompt a physician to treat more aggressively at the diagnosis of chronic GVHD. It is now appreciated that some of these criteria may actually point to persistent manifestations of acute GVHD (late acute, overlap syndrome) rather than pure chronic GVHD (Filipovich et al, 2005;Cho et al, 2009;Jagasia et al, 2009).…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…10,11 The incidence and severity of GVHD were based on a NIH consensus conference to determine GVHD grade. 12 Patients were evaluated for cGVHD if they survived for at least 100 days after HSCT.…”
Section: Definitions and Assessment Of Engraftmentmentioning
confidence: 99%
“…Subsequently, several studies observed that NIH global scoring was useful for predicting NRM and GVHD-specific survival. 7,8 However, relatively few reports have examined the association between NIH global scoring and either relapse or DFS after HSCT.…”
Section: Introductionmentioning
confidence: 99%